Review of Directed motivational currents and language education: Exploring implications for pedagogy; Author: Christine Muir; Publisher: Multilingual Matters, 2020; ISBN: 978-1-78892-884-7; Pages: 252 - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2020)
The construct of a directed motivational current (DMC), or “. . . a surge of motivational energy that seemingly picks an individual up and carries them sometimes unimaginable distances” (p. xvi) was introduced into research on motivation in second and foreign language (L2) learning less than a decade ago (e.g., Dörnyei, Ibrahim, & Muir, 2015; Muir & Dörnyei, 2013). Despite being a relative newcomer to the field, the concept has provided an impulse for empirical investigations which have primarily focused on validating its core assumptions and proposed dimensions using largely qualitative methodology (e.g., Safdari & Maftoon, 2007; Zarrinabadi & Tavakoli, 2017). The book Directed Motivational Currents in Language Education: Implications for Pedagogy by Christine Muir is another valuable addition to this line of inquiry and it can be seen in a way as a follow-up to and extension of the monograph Motivational Currents in Language Learning: Frameworks for Focused Interventions that she co-authored with Zoltán Dörnyei and Alastair Henry in 2016. Since I had the opportunity to write a review of this volume for Studies in Second Language Learning and Teaching (Pawlak, 2017), I was all the more curious to see how research on DMCs has progressed and what promise it currently holds for L2 pedagogy. Therefore, the moment the publisher contacted me with the suggestion that SSLLT might be a good venue for a review, I immediately jumped on the offer and simply felt compelled to take on this task myself. I have to say from the get-go that the book has lived up to my expectations and, although I might be somewhat skeptical about some of the implications for classroom practice, I have to admit that Christine Muir’s work represents a so-much-needed step forward in the study of DMCs. This certainly cannot too often be said about all the apparently innovative ideas introduced into the domain of second language acquisition research.